Physico-Chemical Properties and Digestibility of Watermelon Vines Ensiled with Urea and Molasses (Journal of Veterinary Medicine and Animal Production, 2021)
An experiment was undertaken to estimate some physico-chemical properties and nutrients digestibility of watermelon vines ensiled with 2% urea and four different levels of molasses (0%, 5%, 10% and 15%) for 30 days. A completely randomized design with 4X5 (4 levels and 5 incubation period) for factorial arrangements was adopted for executing the experiment. The ensiled materials before and after 8, 15, 22, 30 days of incubation were tested for chemical composition, lactic and acetic acids concentration. In-vitro dry matter digestibility (IVDMD), in-vitro crude protein digestibility (IVCPD) and in-vitro crude fiber digestibility (IVCFD) were measured at the last day of the fermentation period. Addition of molasses and fermentation period had significant (P